Assessing the Effects of Riverbank Inducement on a Shallow Aquifer in Southeastern Wisconsin - (:unkn) unknown (My University, 2015)
The state of Wisconsin is heavily reliant upon groundwater resources. In order to induce river water, implementation of shallow wells with close proximity to river systems is being used as a method to augment groundwater supplies in portions of southeastern Wisconsin. However, river bank wells (RBI) are vulnerable to contamination due to their close interaction with the surface water. The vulnerability increases when induced surface waters contain municipally treated waste water. The objective of this study was to determine the current and potential influences of riverbank inducement, recharge mechanisms of the well field, and to discriminate the sources of sodium and chloride entering the well field. This was accomplished through the use of tracers and groundwater modeling. The tracer suite included major ions, hydrogen and oxygen stable isotopes, bacteria, and personal care products and pharmaceuticals (PPCPs). Inducement of river water into the RBI wells was calculated to be 44-52%. The flow mechanisms were too complex to be explained by dispersivity alone, so the assumption of plug flow was abandoned. Recharge was found to occur in the spring. Sucralose and acesulfame were found to be the most suitable tracers for this system and proved that waste water effluent enters both RBI wells. Waste water effluent was found to be the major source of salt entering the well field with small contribution from road salt runoff. No pathogenic bacteria were entering the well field.
Keywords: Human Fecal Bacterial Indicators; Hydrogen and Oxygen Stable Isotopes; Hydrologic Tracers; Personal Care Products and Pharmaceuticals; Riverbank Inducement; River Groundwater Interactions